The ghost of Machiavelli: an approach to operation Gladio and terrorism in cold war Italy - Ganser, Daniele (Crime, law and social change, 2006)
In 1990, a document was made public in Italy that shed new light on the secret aspects of the Cold War in Western Europe. The document, dated 1 June 1959, had been compiled by the Italian military secret service SIFAR and is entitled "The special forces of SIFAR and Operation Gladio". It explained that a secret stay-behind army linked to NATO had been set up in Italy for the purpose of unconventional warfare. Ever since, there have been allegations in Italy that the Gladio stay-behind army was linked to acts of terrorism during the Cold War. Despite their importance for criminal, legal and social investigations into the secret history of the Cold War, these questions have received next to no attention among the English-speaking research community since the documents' discovery, partly due to language barriers. With no claim to deal with the stay-behind armies in an exhaustive manner, this essay attempts to analyse and contextualise the Italian data.